(3eLehYI aj GdgfOSIs - (3KGhRhSjhSs
(3ChdgG (B:s
(3GdcJGH ebGdJGf KdGKI hKdGKhf TcdkG GdTeS JJMQc MQcI eYJOjdI hJSei OGFQI GdTeSjI ReGf GdfgGQ s
(3BNQgG (B:s
(3hPdc eG GQOfGg Je cJGH KGhQjhSjhS ai Gddjd hGdfgGQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfi YTQs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1401s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs